2005
DOI: 10.1371/journal.ppat.0010019
|View full text |Cite
|
Sign up to set email alerts
|

Anthrax Lethal Toxin-Mediated Killing of Human and Murine Dendritic Cells Impairs the Adaptive Immune Response

Abstract: Many pathogens have acquired strategies to combat the immune response. Bacillus anthracis interferes with host defenses by releasing anthrax lethal toxin (LT), which inactivates mitogen-activated protein kinase pathways, rendering dendritic cells (DCs) and T lymphocytes nonresponsive to immune stimulation. However, these cell types are considered resistant to killing by LT. Here we show that LT kills primary human DCs in vitro, and murine DCs in vitro and in vivo. Kinetics of LT-mediated killing of murine DCs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
103
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(109 citation statements)
references
References 39 publications
(60 reference statements)
5
103
1
Order By: Relevance
“…32 However, the theory that Nalp1b and caspase-1 control LT-induced necrosis in murine macrophages is challenged by studies using caspase-1 inhibitors, which failed to block LT killing. 18,36,37 Here we show that macrophages derived from C57BL/6, DBA/2 and AKR strains, previously described as "resistant" to LT-mediated cell killing, are actually susceptible to LT-induced cell death by apoptosis. This finding appears to be applicable in vivo, as LT triggered depletion of splenic macrophages in C57BL/6 mice.…”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…32 However, the theory that Nalp1b and caspase-1 control LT-induced necrosis in murine macrophages is challenged by studies using caspase-1 inhibitors, which failed to block LT killing. 18,36,37 Here we show that macrophages derived from C57BL/6, DBA/2 and AKR strains, previously described as "resistant" to LT-mediated cell killing, are actually susceptible to LT-induced cell death by apoptosis. This finding appears to be applicable in vivo, as LT triggered depletion of splenic macrophages in C57BL/6 mice.…”
Section: Introductionmentioning
confidence: 66%
“…17 Despite the broad entry and activity of LT, it selectively kills only a few cell types. 2,[18][19][20][21][22][23][24] As MAPKK cleavage also occurs in cells that are not killed by LT, MAPKK cleavage is not sufficient for LT killing, and possibly not even required for this process. 24 We have previously shown that human and murine dendritic cells (DCs) are killed by LT in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations